Influence of TiO2 content on the optoelectronic performance of PHPMA nanocomposites - Kaya, Esin; Kavsut, Mehmet Salih (Elsevier, 2026)
The incorporation of nanoscale TiO2 particles into polymer matrices has emerged as an effective strategy enhancing the optical and dielectric properties of functional materials. In this study, PHPMA (poly(2-hydrox-ypropyl methacrylate)/TiO2 nanocomposites were prepared by two different methods. In the first method, PHPMA was physically mixed with TiO2 nanoparticles at different weight percentages (1, 5, and 10 wt%). In the second method, TiO2 nanoparticles were initially functionalized with 3-(methacryloyloxy)propyl trimethoxysilane (MPS), and subsequently, HPMA was polymerized from the modified surface via free radical polymerization to obtain PHPMA-g-TiO2. A gradual increase in TiO2 content within the PHPMA matrix led to significant enhancements in the refractive index (from 1.12 to 2.10 at 700 nm), optical conductivity (from 3.6 & times; 10-7to 1.55 & times; 10-6 S cm-1), and dielectric constant (from 1.28 to 4.22). Notably, the grafted nanocomposite exhibited the highest performance, with a refractive index of 2.61, an optical conductivity of 2.29 & times; 10-5 S cm-1, and dielectric constant of 6.78. Simultaneously, the optical band gap decreased from 3.38 eV for neat PHPMA 2.28 eV for the 10% TiO2/PHPMA nanocomposite and further to 1.98 eV in the grafted structure. Additionally, thermal stability in the nanocomposites also improved significantly with increasing TiO2 content. The grafted nanocomposite, exhibiting the highest performance, enhanced light-matter interaction, broadened the spectral response into the visible-NIR region and exhibited superior optoelectronic properties by significantly increasing wavelength selectivity. Overall, the findings underscore the critical role of both TiO2 loading and synthesis strategy in optimizing PHPMA-based nanocomposites for advanced photonic, UV-shielding, and NIR-sensing applications.
Keywords: Polymeric Nanocomposites; Titanium Dioxide; Optical Properties; Refractive Index; Band Gap; Dielectric Properties